Peningkatan Literasi Digital Masyarakat Kuin Cerucuk dalam Menghadapi Hoaks di Era Digital: Enhancing Digital Literacy among Kuin Cerucuk Residents to Combat Hoaxes in the Digital Era - Maghfiroh, Sahara; Alhally, Arafat; Muhamad, Said (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
In the rapidly developing digital era, the spread of hoax information has become a serious threat to society, especially in the contexts of social, political, and health issues. The community service program Digital Savvy Citizens Wisely Face Hoaxes" aimed to improve the digital literacy of the residents of Kelurahan Kuin Cerucuk, Banjarmasin, in recognizing and handling hoaxes. This program was conducted on June 27, 2025, involving 41 participants. The methods used included socialization through lectures, discussions, and hands-on simulations for verifying information using digital platforms. Evaluation was conducted using pre- and post-tests to measure increases in participants' knowledge of hoaxes and information verification. The evaluation results showed a significant improvement in participants' ability to verify information. Before the activity, 39% of participants tended to trust information without verification, but after the activity, only 2% remained the same. Additionally, participants' awareness of verifying information increased from 20% to 78%. This program successfully enhanced the community's understanding of the importance of critical thinking and of verifying information before sharing it, thereby reducing the spread of hoaxes in the digital environment. It is hoped that this activity can be continued with a broader reach and greater interactive media involvement to accelerate learning in the future.